CERTAIN PROPERTIES OF CALCIUM HYDROXYAPATITE FROM SKIPJACK TUNA BONE (Katsuwonus pelamis) - Hy, Le Ho Khanh; Ky, Pham Xuan; Ha, Dao Viet; Hong, Nguyen Thu; Vy, Phan Bao; Thiet, Doan Thi; Anh, Nguyen Phuong (Vietnam Journal of Marine Science and Technology, 2019)
This paper is concerned with certain properties of calcium hydroxyapatite from skipjack tuna bone (Katsuwonus pelamis) which are by-products of fish export industry. Hydroxyapatite Ca10(PO4)6(OH)2 and β-tricalcium phosphate Ca3(PO4)2, the high-value compounds, have been successfully extracted from skipjack tuna bones. The bones were heated at different temperatures of 600oC, 900oC, 1200oC. While at 600oC hydroxyapatites were obtained with Ca/P ratio of 1.658, comparable to the value of 1.67 found in human bone; the hydroxyapatite crystals of average size of 0.25 µm were formed with the same size distribution. In case of heated bone samples at 900°C and 1200°C, the calcium formed were biphasic calcium phosphate composed of hydroxyapatite and β-tricalcium phosphate; the Ca/P ratio was between 1.660–1.665; the calcium crystals of more than 1 µm were highly porous and connected to each other in priority orientation of tube direction.